Development in polymerization shrinkage control of dental light-cured resin composites: a literature review. Issue 4 (16th February 2023) - Guan, Xiaoxu; Zhu, Tianer; Zhang, Denghui
Abstract: Dental light-cured composite resin has been widely used in dental applications because of its easy operation and excellent biocompatibility to achieve the ideal aesthetic outcomes. However, the volume shrinkage generated during the curing process can cause microleakage, hypersensitivity, de-bonding, and fracture of materials or cusps, which would affect treatment efficacy and ultimately reduce the service life of the restoration. Several studies have figured out the mechanism of polymerization shrinkage of light-curable composite resins. Therefore, some strategies have been proposed to control the impact of polymerization shrinkage. This review summarizes the adverse effects, measurement, and mechanism of polymerization shrinkage in light-cured composite resin. It also reviews the studies on development in polymerization shrinkage control strategies in terms of modification of resin matrix, modification of filler, light mode, appropriate filling method and adhesive, and suitable oral temperature and humidity.